The Development and Validation of the Organisational Ethical Behaviour Questionnaire of Medical Representatives - C. Suriyaprakash; Chinnu Stephan (International journal of economic perspectives, 2022)
Ethics has emerged as one of the major issues facing organizations. This focus is perhaps stimulated by an increase in publicity about unethical practices by organizations and their management. Although the literature has many studies on organisational ethical behaviour(Geeta, Pooja& Mishra, 2016), there is a lack of research on examining the factors influencing the organisational ethical behaviour by using qualitative study. The aim of this study was to develop and validate an instrument used to measurethe organisational ethical behaviour of medical representatives in Kerala. To assess the reliability and validity of the instrument, a random sample of 198 medical representatives were selected and the questionnaire was given. On the responses collected, exploratory factor analysis was carried out to ensure the factorial validity of the instrument. Sample adequacy was validated using Kaiser-Meyer-Olkin test. A principle component analysis was applied to extract the factors. The internal consistency and reliability of the factors was assessed using Cronbach alpha. The factorial validity was ensured by performing PCA were the factor loading co-efficient were greater than 0.4 and the cumulative percentage of the variance extracted was 78 percentage. The KMO test ensured the sample adequacy with the value of 0.657.The internal reliability of the questionnaire was reasonable with a Cronbach values greater than 0.75. The study demonstrated that the newly developed instrument has a good level of properties measured as content and factorial validity, internal consistency and reliability.